Open Water Swimming - Munatones, S. (Human Kinetics, 2011)
Product Description by Human Kinetrics: Swim faster, stronger, and more efficiently. Whether you are a dedicated open-water swimmer or a triathlete looking to conquer the sport`s most challenging event, Open Water Swimming is your complete guide to improving your performance and decreasing your time. In Open Water Swimming, renowned marathon swimmer, coach, and commentator Steven Munatones shares his insights and expertise on preparing, training, and competing in open-water events. From triathlon to marathon and all distances in between, you`ll learn these tactics:•Refine your freestyle stroke to improve power, speed, effectiveness, and navigational IQ. •Pace yourself, and conserve energy, for faster finishes. •Train for every event with conditioning programs for short, Olympic, marathon, and triathlon distances. •Shave seconds off your time with professional tactics for starts, turns, feedings, transitions, and finishes. •Incorporate the racing strategies of the most successful swimmers in the sport. •Prepare physically and psychologically for the demands of competition. From the art of efficient pack swimming to the best dryland and pool workouts for improving endurance, strength, and power, Open Water Swimming covers it all. Read it, refer to it, and rely on it for improved results and faster times!